STRATEGIES FOR COMBATING THEFT-BASED CRIME THROUGH ANALYSIS OF INEQUALITY AND POVERTY: A CONCEPTUAL AND PRACTICAL REVIEW - Gunawan Widjaja; Junior B. Gregorius (CV. ADIBA AISHA AMIRA, 2026)
This study aims to examine strategies for combating theft using an analysis of economic inequality and poverty through a literature review. The study examines the complex relationship between social inequality, poverty, and theft, and identifies strategic interventions that have been implemented in a socio-economic context to reduce theft rates. The findings reveal that inequality and poverty are critical factors driving criminal behaviour, necessitating effective interventions that integrate preventive, repressive, and socio-economic empowerment approaches. Strategic recommendations include multi-stakeholder collaboration, improved education, strengthened social systems, and the use of security technology. This approach not only addresses the symptoms but also the root causes of theft crime to create a safe, fair, and inclusive environment.